Pengembangan Kemandirian Pangan Kader PKK Desa Mancilan Berbasis Olahan Pangan Lokal - Anggi Indah Yuliana; Mohamad Nasirudin; Siti Nur Qomariyah (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2025)
Local food development needs to be optimized to realize food self-sufficiency. Mancilan Village has local food sources that have not been utilized properly, namely spinach and rambutan. There needs to be an effort to optimize these food sources through community empowerment activities. This community service activity aims to improve and develop the skills of the PKK Melati Cadre in Mancilan Village in utilizing the local food potential of rambutan and spinach as processed food products. The approach model applied in this community empowerment activity is a participatory approach as well as asset or resource-based community empowerment. The methods used in this activity include workshops, demonstrations, simulations, and FGDs attended by 30 participants. Food processing training activities in the form of spinach noodles and hair nuggets have succeeded in increasing the knowledge and skills of Mancilan Village PKK cadres. The ease of raw materials and the process of making products are supporting factors in product application. On the other hand, based on the hedonic test of spinach noodle and rambutan nugget products, the average shows a positive value in terms of taste, color, aroma, and texture of the product.